Fundamental Issues in the Qualification of Smart and Intelligence in Building Materials Discourse: A Systematic Review - Ikechukwu Ogwu; Zhilin Long; Deuckhang Lee; Xuhui Zhang; Wei Zhang; Moses Okonkwo (Buildings, 2021)
The fundamental notion of ‘smart’ in building materials discourse is responsiveness—the ability of materials to react to environmental stimuli by manifesting a noticeable physical change when there is a difference in the conditions of their immediate surroundings. This notion, however, is also interchanged with ‘intelligence’, which involves an array of control protocols. Notwithstanding, both notions are used synonymously and as occupant comfort and energy efficiency strategies in buildings. The current study aimed to underscore the fundamental issues in the conceptualization of both notions in building materials colloquy by systematic review of published literature following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 checklist. The review revealed that while smart responses are direct, predictable and reversible, requiring no external control system, computer systems and networks which require a constant supply of energy are essential for intelligence. In fact, the relationship between intelligent systems, energy efficiency and occupant comfort depends on external computer control and machine components of learning, resulting in complex systems with longer payback times, whereas smart materials and systems respond directly and immediately without additional energy or occupant control. The discussions present an attempt towards promoting zero additional energy demand for buildings using smart materials.